Vitamin D Supplementation: Association With Serum Cytokines in Pediatric Hematopoietic Stem Cell Transplantation - Olsen, Braden; Bodea, Jessica; Garcia, Angela; Beebe, Kristen; Campbell, Courtney; Schwalbach, Carly; Salzberg, Dana; Miller, Holly; Adams, Roberta; Mirea, Lucia; Castillo, Paul; Horn, Biljana; et al. (Frontiers in Pediatrics, 2022)
Vitamin D deficiency is prevalent in pediatric patients presenting for hematopoietic stem cell transplantation (HSCT) and has been linked to poor clinical outcomes. Using the data from a randomized control trial, in this paper we explore the effects of vitamin D supplementation on circulating cytokine levels during pediatric HSCT (www.clinicaltrials.gov as NCT03176849). A total of 41 children, 20 received Stoss therapy and 21 children received standard of care vitamin D supplementation. Levels of 25(OH)D and 20 cytokines were assessed at baseline and day +30. Significantly (p<0.05) higher levels of mostly proinflammatory cytokines, FGF, GCSF, TNFα, IL1, IL2, IL6, IP10 were detected pre-transplant for patients with low compared to those with normal vitamin D levels. In sex stratified models that compare changes in cytokines between Stoss vs standard of care, females in the Stoss group show greater changes in mostly pro -inflammatory cytokines- IP-10 (p=0.0047), MIG (p=0.009) and RANTES (p=0.0047), IL-2R (p=0.07) and IL-6(p=0.069). Despite a small sample size, these findings suggest vitamin D deficiency affects the pre-transplant cytokine milieu and higher doses of vitamin D (Stoss therapy) appears to influence proinflammatory cytokine responses in a sex specific manner during pediatric HSCT. Larger clinical trials are warranted to validate these results.